Advancing Elementary Vocabulary Education with Wordwall-Based Digital Media - I Komang Yogi Pratama Wedananta; I. G. A. Lokita Purnamika Utami; G. A. P. Suprianti (UIBU, 2024)
In Indonesia, the education curriculum underwent numerous changes, with the most recent being the Merdeka curriculum. Vocabulary was a crucial component in English language learning. This study aimed to develop Wordwall-based learning media for vocabulary using the